The world's largest climate change experiment needs you! (Geographical (Geographical Magazine Ltd.), 2006)
The article reports that Oxford University and British Broadcasting Corp. are organizing the world's largest climate change experiment in an attempt to predict how increased levels of greenhouse gases in the atmosphere will affect global temperatures. Because of the complexity of world climate even the world's largest supercomputers are unable to deal with the volume of calculations required. Scientists are hoping to use the power of thousands of home personal computers worldwide through a technique called distributed computing.